THU0064 Endothelial Progenitor Cell Biology in Ankylosing Spondylitis. (10th June 2014) - Syngle, A.; Verma, I.; Krishan, P.
Abstract : Background: Endothelial progenitor cells (EPCs) are unique populations which have reparative potential in overcoming the endothelial damage and reducing cardiovascular risk 1 . Patients with ankylosing spondylitis (AS) have increased risk of cardiovascular morbidity and mortality. However, EPCs have not been investigated in AS. Objectives: The aim of this study was to investigate the endothelial progenitor cell population in AS patients and its potential relationships with disease variables. Methods: Endothelial progenitor cells were measured in peripheral blood samples from 20 AS and 20 healthy controls by flow cytometry on the basis of CD34 and CD133 expression. Disease severity was evaluated using Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). Functional ability was monitored by using Bath Ankylosing Spondylitis Functional Index (BASFI). Results: EPCs were depleted in AS as compared to the healthy controls (CD34+/CD133+: 0.027±0.010% vs. 0.044±0.011%, p<0.001) (Figure 1 A). EPC depletion was significantly associated with disease duration (r= -0.52, p=0.01) (Figure 1B), BASDAI (r= -0.45, p=0.04) (Figure 1C) and CRP (r= -0.5, p=0.01). Conclusions: This is the first study to demonstrate endothelial progenitor cells depletion in AS patients. EPCs depletion inversely correlates with disease duration, disease severity and inflammation, suggesting the pivotal role of inflammation in depletion of EPCs. EPC would possibly also serve as a therapeutic target for preventing cardiovascular disease in AS. References: Hill JM et al. N Engl J Med. 2003; 348:593–600. Acknowledgements: This study has been supported by a Research Fellowship from University Grant Commission, New Delhi (Govt. of India) [No. F.10-15/2007 (SA-I)]. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5181